A Multifactorial Model of Dyslexia: Evidence from Executive Functions and Phonological‐based Treatments. Issue 3 (30th June 2020) - Pasqualotto, Angela; Venuti, Paola
Abstract: In this research, we examined the responsiveness to treatment in 49 Italian children with Dyslexia. In part A, we compare the efficacy of a phonological‐based treatment (Ph‐T) with a cognitive training of executive functions (CT). In part B, we investigate whether a sequential treatment (CT+Ph‐T) has a larger remedial effect compared to the pure phonological‐based treatment (Ph‐T + Ph‐T). Results after 24 hours of treatment showed significant improvements in the executive functions (EFs) for the sequential group only. Considering reading accuracy, children benefited significantly from both treatments; however, only the sequential group significantly improved in reading speed. Crucially, the reading gains appeared to be related to improvements in the EFs, supporting a multifactorial model of this disorder. The aforementioned findings suggest that the combination of cognitive training of EFs with a phonological‐based treatment can be used effectively in rehabilitating dyslexia.